Biochemical indicators of cows’ blood serum at lesions in the hoof area - Klymas, A. (Scientific Progress & Innovations, 2025)
Health and productivity of cows is considerably determined by the condition of the extremities’ distal section. It is known that to ensure animals’ high productivity, it is necessary for them to move freely in space, which directly depends on the physiological condition of hooves. In cases when the upset of hooves’ anatomical parameters occurred, inflammatory processes including purulent ones take place in cows’ organism. Any inflammatory process in the animal body irrespective of the place of its localization causes changes in homeostasis. With the help of screening studies of diseased animals’ blood, it is possible to clarify the severity of the pathological process and make scientifically grounded choice of the treatment optimal regimen. Therefore, the purpose of the conducted research was to characterize the changes in cows’ blood serum biochemical parameters at purulent lesions in the hoof area. The clinical examinations of cows were conducted on “Agro-ecology” private farm, laboratory tests of blood serum were made in the Regional State Laboratory of the State Food Products’ Consumer Service of Poltava region. It was found by the studies that in the blood serum of cows diagnosed with purulent lesions in the hoof area, the content of carotene in the group made 0.042 mg/100 cm3 on the average, which turned out to be by 43.2 % lower (р<0.01) compared to the similar indicator in the clinically healthy animals. At the same time, at the background of carotene content decrease in the blood serum of the diseased cows, the probable increase in total protein was fixed. In particular, the total protein content in the blood serum made 7.8 g/100 cm3 on the average, which was by 12.8 % (р<0.05) higher than in the cows of the control group. Besides, the decrease in the content of the total calcium, the concentration of inorganic phosphorus, and acid content was detected in the blood serum of the diseased cows. For example, at purulent lesion in the hoof area, it was found that in the blood serum of cows the content of total calcium in the group made 9.1 mg/100 cm3, the concentration of inorganic phosphorus – 4.8 mg/100 cm3, acid content in the blood serum – 236.4 mg/100 cm3 on the average, which was lower than the similar indicators in the cows of the control group by 5.2 (р<0.05), 7.7 (р<0.01) and 10.7 % (р< 0.05), respectively.